Insulin-Induced Normoglycemia Reduces Islet Number Needed to Achieve Normoglycemia after Allogeneic Islet Transplantation in Diabetic Mice - Juan C. Ferrer-Garcia; Juan F. Merino-Torres; Gema Pérez Bermejo; Carmen Herrera-Vela; Jose L. Ponce-Marco; Francisco Piñon-Selles (Cell Transplantation, 2003)
The Edmonton protocol established that insulin independence could be reached with the transplantation of an appropriate number of islet cells. However, to effect a cure, islets from two or three pancreases are needed. The aim of this study was to examine whether normoglycemia, with insulin treatment before and after transplantation, reduces the islet number needed to achieve normoglycemia in allogeneic islet transplantation. Swiss mice were used as donors and recipients. Diabetes was induced by IP administration of streptozotocin (180 mg/kg BW). Diabetic mice were transplanted with 300 (n = 16), 400 (n = 16), or 500 (n = 16) islets under the left kidney capsule. For every group, half the animals were kept normoglycemic with insulin treatment from day 4 before transplantation to day 10 after transplantation. At the end of the study, all normoglycemic mice were given an IP glucose tolerance test (IPGTT). For statistical analysis, paired or unpaired Student's t-test or ANOVA was used. Only insulin-treated mice achieved normoglycemia by the end of the study (37.5% of animals transplanted with 400 islets and 50% transplanted with 300 or 500 islets). At the end of the study, normoglycemic mice transplanted with 300 allogeneic islets showed better glycosylated hemoglobin (HbA 1C ) than did normoglycemic mice transplanted with 500 islets (300 islets: 2.7 ± 0.2%; 500 islets: 3.6 ± 0.2%; p < 0.05). After the IPGTT, insulin-treated mice transplanted with 500 islets showed abnormal glucose tolerance; however, insulin-treated mice transplanted with 300 or 400 islets showed normal glucose tolerance. Insulin treatment reduced the islet number needed to achieve normoglycemia in allogeneic islet transplantation. The HbA 1C and IPGTT results suggest that transplanting smaller numbers of allogeneic islets improves β-cell function; some studies suggest that this may be due to lower immunogenicity, hypoxia, and inflammation.